The Relationship between Family Support and Suicide Ideation in College Students - Adiguna, Drajat; Elita, Veny; Aziz, Ari Rahmat (CV. Rayyan Dwi Bharata, 2024)
Introduction: Suicide is the second leading cause of death among teenagers and early adults. Suicidal behavior is related to the family support provided. The aim of this research is to determine the relationship between family support and suicidal ideation among students at a university in Pekanbaru, Riau. Method: This research uses a descriptive correlation design using a cross-sectional approach. The sample consisted of 100 respondents taken using the accidental sampling technique. The measuring instruments used were the Perceived Social Support-Family Scale (PSS-Fa) questionnaire for family support and the Beck Scale for Suicide Ideation (BSS) for suicidal ideation. Data analysis used the chi-square test. Results: It is known that the majority of respondents have family support in the good and sufficient categories with the same number, namely 39 respondents (39.0%). For the variable suicidal ideation, the majority of respondents were in the low risk category totaling 52 respondents (52.0%), while the remainder were in the high risk category totaling 28 respondents (28.0%) and very high risk totaling 20 respondents (20 .0%). The results of statistical tests show that there is a relationship between family support and suicidal ideation in students (p value 0.021 α 0.05). Conclusion: Family support has a significant relationship with suicidal ideation.